Intestinal parasitism in children of six schools, urban and rural areas, of Jipijapa Canton, Ecuador - Anita Maria Murillo Zavala; Katherine Castro Ponce; Zulbey Rivero de Rodríguez; Angela Bracho Mora (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
Intestinal parasites to be a public health problem, especially in people with limited resources and in preschool and school age due to immunological immaturity and their hygienic habits are still developing. The aim of the study was to determine the prevalence of intestinal parasites in six schools children belonging to Canton Jipijapa, Ecuador. For this, 6 educational units from different parishes, both urban and rural. Considering children between the ages of 1 and 12, with a total population of 647 children. All children underwent a direct coproparasitological examination and, Ji-square tests were applied to verify the significance between the variables age, sex, parasitized or not with respect to the location of educational institutions. Results: A general prevalence of 41.7% was observed, with chromist/protozoa prevailing over helminths, with a predominance of 53.2% for the school age group and polyparasitism. The Entamoeba complex (41.8%) was the most frequently identified species, Blastocystis sp. and E. coli. Giardia lamblia was the most frequently isolated pathogen. The protozoa prevailed and in the urban population, with significant difference. More studies are needed to know the determinants of parasites in these populations to establish health policies.